Feeding spectra and activity of the freshwater crab Trichodactylus kensleyi (Decapoda: Brachyura: Trichodactylidae) at La Plata basin - Williner, Verónica (2014)
Background: In inland water systems, it is important to characterize the trophic links in order to identify the ‘trophic species’ and, from the studies of functional diversity, understand the dynamics of matter and energy in these environments. The aim of this study is to analyze the natural diet of Trichodactylus kensleyi of subtropical rainforest streams and corroborate the temporal variation in the trophic activity during day hours. Results: A total of 15 major taxonomic groups were recognized in gut contents. The index of relative importance identified the following main prey items in decreasing order of importance: vegetal remains, oligochaetes, chironomid larvae, and algae. A significant difference was found in the amount of full stomachs during day hours showing a less trophic activity at midday and afternoon. The index of relative importance values evidenced the consumption of different prey according to day moments. Results of the gut content indicate that T. kensleyi is an omnivorous crab like other trichodactylid species. Opportunistic behavior is revealed by the ingestion of organisms abundant in streams such as oligochaetes and chironomid larvae. The consumption of allochthonous plant debris shows the importance of this crab as shredder in subtropical streams. However, the effective assimilation of plant matter is yet unknown in trichodactylid crabs. Conclusions: This research provides knowledge that complements previous studies about trophic relationships of trichodactylid crabs and supported the importance of T. kensleyi in the transference of energy and matter from benthic community and riparian sources to superior trophic levels using both macro- and microfauna.